Еволюція економічної інтеграції в країнах Європи : монографія - Беренда Сергій Васильович (Харків : Харківський національний університет імені В. Н. Каразіна, 2012)
У монографії висвітлені можливості використання положень еволюційного вчення в економіці та застосування їх в дослідженні економічної інтеграції. Автор намагається ввести в науковий обіг дослідження економічної інтеграції міждисциплінарний підхід. У дослідженні встановлено основні детермінанти цього процесу, зокрема на основі поняття регіональної економічної ентропії. В дослідженні проаналізовано та розраховано гравітаційний потенціал економік країн ЄС та встановлено місце України серед них.

Copenhagen and Maastricht criteria for membership and convergence in the EU are considered as a measure of information or management aimed at the arrangement of the EU. This reaction entropy - disorderly system, so do not give the criteria for membership to unbalance the system and maintain a sufficient level of entropy so that the EU could function. The study found the main determinants of economic integration at EU level is given an attempt to quantify this process. The author assesses the status, dynamics and prospects of the factors of socio-economic integration of member countries of the integration of interaction in Europe. Analyzed and calculated gravitational potential of the economies of EU countries, and found the place of Ukraine among them. This indicates a potential lack of institutionalization of relations between Ukraine and EU and the need to form an FTA.
Навчальне видання
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; внутрішньогалузева торгівля; ентропія соціально-економічних систем; господарська інтеграція; форми економічної інтеграції; еволюція економічної інтеграції; economic integration; intra-industry trade; the entropy of socio-economic systems; economic integration; the evolution of economic integration